(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
Abstract: The main aim of this empirical research is to prove that the Emotional Intelligence of senior executives exerts a direct and positive effect upon the Innovation within the different enterprises. The study has been managed to a total figure of 139 senior executives belonging to Spanish Companies from a vast wide range of activities and whose have answered a survey of 22 items. In addition to validating the conceptual model, the outcome from this empirical analysis applying the Structural Equation Model have confirmed the “ Starting hypothesis”: “The Emotional Intelligence of Senior Executives exert a direct and positive effect upon products innovation and upon processes innovation within the companies.